b - Yousaf, Nosheen [Ed.]; Anwar, Waseem [Ed.] (Newyork : Routledge, 2022)
This volume looks at the implications of transcultural humanities in South Asia. It is becoming a crucial area of research within literary and cultural studies, with its indeterminate periodisation, its temporal and spatial non-linearity, its territoriality and intersectionality. Drawing on contributors from around the globe, the entries look at literature and poetics, theory and praxis, borders and nations, politics, partition, gender and sexuality, the environment, representations in art, and pedagogy and the transcultural classroom. Using key literary and cultural examples and case studies, the contributors look at current developments in postcolonial, transcultural and transnational standpoints and their possible educational outcomes. This broad and comprehensive book also speaks volumes to the value of the humanities, and the significance of South Asian contexts. It will be of particular interest to those working on postcolonial studies, literary studies, Asian Studies and more"-- Provided by publisher.
Keywords: South Asian literature; History and criticism Humanities -- South Asia Postcolonialism and the arts -- South Asia